2014
DOI: 10.2478/s13533-012-0188-6
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion modeling of air pollutants in the atmosphere: a review

Abstract: Modeling of dispersion of air pollutants in the atmosphere is one of the most important and challenging scientific problems. There are several natural and anthropogenic events where passive or chemically active compounds are emitted into the atmosphere. The effect of these chemical species can have serious impacts on our environment and human health. Modeling the dispersion of air pollutants can predict this effect. Therefore, development of various model strategies is a key element for the governmental and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 130 publications
0
107
0
9
Order By: Relevance
“…[3]). While Gaussian-based and Lagrangian models are well established for the latter, Leel} ossy et al [4] identified that there is currently no accurate near-range atmospheric dispersion modeling approach available which complies with this short runtime.…”
Section: Introductionmentioning
confidence: 94%
“…[3]). While Gaussian-based and Lagrangian models are well established for the latter, Leel} ossy et al [4] identified that there is currently no accurate near-range atmospheric dispersion modeling approach available which complies with this short runtime.…”
Section: Introductionmentioning
confidence: 94%
“…CFD models require a complex parameterisation compared to traditional Gaussian dispersion models, but they have been shown to provide increased accuracy over complex terrain (Buccolieri and Sabatino, 2011), which can be considered to be the case over the landfill site. Resolving three-dimensional distributions of wind flow and gas concentration in the modelling domain on small scales makes them an attractive choice compared to Lagrangian dispersion models (Leelőssy et al, 2014). The CFD model presented in this study has previously been evaluated by a comparison exercise against a wind tunnel experiment (Jeanjean et al, 2015) and measurements from an urban monitoring station .…”
Section: Cfd Modelmentioning
confidence: 99%
“…[1,2] are used in risk analysis procedures. Easy and fast estimation have some major limitation: they simulate emergency scenario in open, flat terrain without any obstacles and with steady wind [3].…”
Section: Introductionmentioning
confidence: 99%